Does the environment matter? a case study of the International Islamic University Malaysia - Sulaiman, Maliah; Abdul Rahman, N. (Universiti Malaysia Sarawak, 2013)
The ability of an organization to manage its environmental performance is emerging as a strategic issue for many organizations. Institutions of higher learning are no exception. Given that a university is a consumer of natural resources and a producer of waste (Flint, 2001), it is imperative that environmental cost information is made visible to the management of the organization so that the impact can be manages more effectively. Environmental management accounting (EMA) is often lauded as the tool "capture" environmental cost information. However, before such a tool can be implemented, it is important to examine if indeed the university community is aware of environmental issues. If they are, what types of information do they perceive as important to enable them to better address the impact of their activities on the environmental. Using the International Islamic University Malaysia (IIUM) as the case, our study examined two pertinent issues; the extent the university community is aware of environmental issues and EMA and their need for environmental cost information. Data was collected using a questionnaire survey. The results revealed a moderate level of awareness on environmental matters amongst IIUM staff. Most were aware of environmental management system (EMS) but not EMA. Further, they perceive environmental cost information to be useful to manage the impact of their activities on the environment. In particular, they felt that information on the use of paper is important.